PS02.030: CLINICAL COURSE OF PATIENTS WITH COMPLETE RESPONSE BY CHEMORADIOTHERAPY FOR LOCALLY ADVANCED ESOPHAGIEAL CANCER. (14th September 2018) - Tamura, Shigeyuki; Matsuyama, Jin; Nagai, Kenichi; Imamura, Hiroki; Yagi, Yuriko; Mokutani, Yukako; Hashimoto, Yasuji; Hirose, Hajime; Kubota, Masaru; Ide, Yoshihito; Fukushima, Yukio; Sasaki, Yo
Abstract: Background: Definitive chemoradiotherapy (dCRT) is one of the treatment strategies for patients with locally advanced esophageal squamous cell carcinoma (LA-ESCC). In this report, we investigated the timing, pattern of recurrence, and prognosis in patients with LA-ESCC who achieved clinical complete response (cCR) following dCRT. Methods: dCRT was performed for 71 patients with LA-ESCC from April 2006 and December 2017. We retrospectively examined the clinical records of 27 patients (38%) with ESCC who achieved cCR following dCRT assessed by the Response Evaluation Criteria in Solid Tumors (RECIST). These patients were classified into two groups: 19 patients (Group A) who did not recognize recurrence thereafter and 8 cases (Group B) who were confirmed to have recurred until Deccember 2017. Clinicopathological features and clinical course for two groups were examined. Results: Clinical stages before treatment were cT1/2/3/4 = 7/3/6/3 cases, cN0/1/2/3 = 8/3/6/2, cM0/1 = 18/1 and cStage I/II/III/IV = 6/4/6/3 in Group A, and cT1/2/3/4 = 1/3/2/2, cN0/1/2/3 = 1/2/4/1, cM0/1 = 8/0, cStage I/II/III/IV = 1/0/5/2 in Group B, respectively. Patients in Group B had more advanced cases than Group A. In group A, 16 out of 19 patients (84%) are still alive without recurrence and 3 have died because of hypopharyngial cancer, lung cancer, and senility, respectively. Double cancers were confirmed in 12 patients (63%) including 6 head and neck cancers. In Group B, the recurrences were confirmed at 7–26 months (Median: 12.5M) from the diagnosis of cCR. Six out of 8 patients (6/8:75%) had the recurrence of mediastinal lymph nodes. In Group B, 6 out of 8 cases (75%) confirmed death, and the period from recurrence to death was 5–18 months (median: 9.5M). Conclusion: After cCR was obtained by dCRT, recurrence was observed in 8/27 cases (29.6%) in about 13 months. In patients with recurrence, 75% of patients had mediastinal lymph node recurrence and had poor prognosis of about 10 months. Also in patients without recurrence, double cancers were observed in 12/19 cases, suggesting the importance of surveillance for the purpose of 2 nd primary cancer screening. Disclosure: All authors have declared no conflicts of interest.